Peraturan Kraton Yogyakarta Yang Tak Lagi Jadul (Suatu Analisis terhadap Pembaharuan Teknik, Format dan Muatan Dawuh Dalem di Kraton Yogyakarta) - Beni, Rozi (Jurnal Hukum & Pembangunan, 2023)
In the midst of the rapid development of the conception and implementation of a modern and democratic government structure, the Ngayogyakarta Hadiningrat Sultanate was able to preserve its customary laws, including regarding governance and government structure in a monarchical system regulated in the Kraton's statutory regulations. Customary law, such as Dawuh Dalem, is often considered ancient, out of date, only important for legal historians, and other skeptical views. However, in reality, customary law is still alive with various reforms. In this normative research, we discuss the renewal of the internal statutory regulations of the Yogyakarta Palace, called Dawuh Dalem. The Dawuh Dalem studied is Dawuh Dalem Number: 01 / DD / HB10 / ALIP. 1955.2022 Date Kaping 14 Pasa, Alip 1955, Surya Kaping 16 April 2022 Chapter Pranatan Anyar Tata Assemble Printing Palace Ngayogyakarta Hadiningrat Ngganti Dawuh Dalem Figure: 01/Dd/Hb The Dalem is an internal regulation of the Yogyakarta Palace, but the preparation technique, format and content of the Dawuh Dalem have adopted and are in accordance with the drafting rules and framework of state laws and regulations as regulated in the Law on the Establishment of Legislation. Apart from that, the contents of Dawuh Dalem also include the philosophical basis, vision, mission and goals, as well as the distribution of job duties within the Government of the Ngayogyakarta Sultanate. This shows that, although the government system in the Kraton adheres to a monarchical system, it has succeeded in reforming the Kraton's regulations by adopting the rules of modern and democratic state legislation. Dawuh Dalem is open to be developed, maintained and renewed. More than that, the regulatory content in Dawuh Dalem Kraton which contains guidelines for behavior, justice, protection, ethical behavior, anti-corruption and other universal values, shows that in fact customary law is relevant and connected and can be a source of national and international law.